Long Terminal Repeats of Gammaretroviruses Retain Stable Expression after Integration Retargeting - Miklík, Dalibor; Slavková, Martina; Kučerová, Dana; Mekadim, Chahrazed; Mrázek, Jakub; Hejnar, Jiří (Viruses, 2024)
Retroviruses integrate into the genomes of infected host cells to form proviruses, a genetic platform for stable viral gene expression. Epigenetic silencing can, however, hamper proviral transcriptional activity. As gammaretroviruses (γRVs) preferentially integrate into active promoter and enhancer sites, the high transcriptional activity of γRVs can be attributed to this integration preference. In addition, long terminal repeats (LTRs) of some γRVs were shown to act as potent promoters by themselves. Here, we investigate the capacity of different γRV LTRs to drive stable expression within a non-preferred epigenomic environment in the context of diverse retroviral vectors. We demonstrate that different γRV LTRs are either rapidly silenced or remain active for long periods of time with a predominantly active proviral population under normal and retargeted integration. As an alternative to the established γRV systems, the feline leukemia virus and koala retrovirus LTRs are able to drive stable, albeit intensity-diverse, transgene expression. Overall, we show that despite the occurrence of rapid silencing events, most γRV LTRs can drive stable expression outside of their preferred chromatin landscape after retrovirus integrations.
Keywords: Gammaretrovirus; Humans; Promoter Regions, Genetic; genetické vektory; Transgenes; vectors; lidé; Terminal Repeat Sequences; zvířata; transgeny; regulace exprese virových genů; buněčné linie; epigenetics; proviry; Gene Silencing; umlčování genů; Cell Line; retrovirus; integration site; silencing; koncové repetice; integrace viru; Genetic Vectors; Animals; Gene Expression Regulation, Viral; promotorové oblasti (genetika); Virus Integration; expression; Proviruses